2014
DOI: 10.1007/978-3-319-05110-9
|View full text |Cite
|
Sign up to set email alerts
|

Basics of Functional Analysis with Bicomplex Scalars, and Bicomplex Schur Analysis

Abstract: Contents Introduction Chapter 1. Bicomplex and hyperbolic numbers 1.1. Bicomplex numbers 1.2. Conjugations and moduli. 1.3. The Euclidean norm on BC 1.4. Idempotent decompositions 1.5. A partial order on D and a hyperbolic-valued norm Chapter 2. Bicomplex functions and matrices 2.1. Bicomplex holomorphic functions 2.2. Bicomplex matrices Chapter 3. BC-modules 3.1. BC-modules and involutions on them 3.2. Constructing a a BC-module from two complex linear spaces. Chapter 4. Norms and inner products on BC-modules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
134
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 61 publications
0
134
0
1
Order By: Relevance
“…Quite recently, there has been a significant resurgence of interest in the theory of functions of bicomplex variables, where some of these ideas are further expanded and discussed. Without any attempt to completeness, we should at least quote [3], [5], [11], [12], [13], [17] and [18].…”
Section: The Case N =mentioning
confidence: 99%
“…Quite recently, there has been a significant resurgence of interest in the theory of functions of bicomplex variables, where some of these ideas are further expanded and discussed. Without any attempt to completeness, we should at least quote [3], [5], [11], [12], [13], [17] and [18].…”
Section: The Case N =mentioning
confidence: 99%
“…The order defined in Theorem 3.1 was considered in [1] to introduce a new hyperbolic-valued norm on the set of bicomplex numbers.…”
Section: Archimedean F -Algebra Structure Theorem the Algebra Of Hypementioning
confidence: 99%
“…Elizarraràs et al [1,11] introduced elementary functions, such as polynomials, exponentials and trigonometric functions in this algebra, as well as their inverses, something that is not possible in the case of quaternions. They showed that any pair of holomorphic functions admits derivative in the sense of bicomplex numbers.…”
Section: Introductionmentioning
confidence: 99%